Characterization of coffee (Coffea arabica) husk lignin and degradation products obtained after oxygen and alkali addition - de Carvalho Oliveira, Fernanda; Srinivas, Keerthi; Helms, Gregory L.; Isern, Nancy G.; Cort, John R.; Gonçalves, Adilson Roberto [UNESP]; Ahring, Birgitte Kiær (Elsevier, 2018)
The full use of biomass in future biorefineries has stimulated studies on utilization of lignin from agricultural crops, such as coffee husk, a major residue from coffee processing. This study focuses on characterizing the lignin obtained from coffee husk and its further wet oxidation products as a function of alkali loading, temperature and residence time. The lignin fraction after diluted acid and alkali pretreatments is composed primarily of p-hydroxylphenyl units (≥49%), with fewer guaiacyl and syringyl units. Linkages appear to be mainly β-O-4 ether linkages. Thermal degradation of pretreated lignin during wet oxidation occurred in two stages. Carboxylic acids were the main degradation product. Due to the condensed structure of this lignin, relatively low yields of aromatic aldehydes were achieved, except with temperatures over 210 °C, 5 min residence time and 11.7 wt% NaOH. Optimization of the pretreatment and oxidation parameters are important to maximizing yield of high-value bioproducts from lignin.
Keywords: Alkaline conditions; Biorefinery; Coffee husk; Lignin; Wet oxidation